Effect of some peel extracts on the corrosion behavior of aluminum alloy in alkaline medium - Chaubey N.; Singh V.K.; Quraishi M.A. (My University, 2025)
Introduction: The inhibition performance of three peels, for instance Pisum sativum (PS), Solanum tuberosum (ST), and Citrus reticulata (CR), on aluminum alloy (AA) in 1 M NaOH solution was investigated using weight loss, electrochemical impedance spectroscopy (EIS), linear polarization, and potentiodynamic polarization techniques (Tafel). Results: It was found that these three peel extracts exhibit very good performance on AA in alkaline medium. PS exhibited maximum inhibition efficiency (η%) of 94.5 % at 1.5 g/L. The effective protection of AA in inhibited system was investigated using scanning electron microscopy (SEM) and atomic force microscopy (AFM). Conclusion: The adsorption of inhibitors on AA surface obeyed the Langmuir’s adsorption isotherm. Potentiodynamic polarization studies showed mixed mode of corrosion inhibition for all the inhibitors. SEM and AFM complemented well with those obtained from weight loss and electrochemical studies. © 2015, The Author(s).